P11 Screening for NTM lung disease in adult non-CF adult bronchiectasis patients – physician survey in germany, UK, italy, france and the netherlands. (December 2018) - Wagner, D; van Ingen, J; van der Laan, R; Obradovic, M
Abstract : Background: Nontuberculous mycobacteria (NTM) lung disease has been increasing globally with bronchiectasis being a strong risk factor. The objective of this study was to evaluate the current screening practices of physicians for NTM disease in adult patients with non-CF bronchiectasis (NCFB). Method: We conducted an online survey with 280 physicians treating adult non-CF bronchiectasis patients in Germany, UK, Italy, France and the Netherlands. Respondents had to spend at least 80% of their time in the hospital setting and manage N³10 adult NCFB patients in previous 12 months. Results: 85% (range: 80%–88%) of surveyed physicians tested at least some of their NCFB patients for NTM infection. In total 51% (range: 40% [France] – 70% [Netherlands]) of NCFB patients managed by these respondents were tested for NTM infection and 17% of those (range: 8% [Netherlands] – 21% [Germany]) – were stated to have tested positive. The NTM infection was mostly suspected by physicians due to radiology exams or physical features of the lung (82%). Close to half of NCFB patients are tested for NTM on diagnosis or initial presentation. 64% of respondents (range: 52%–76%) test for NTM in at-risk patients with NCFB at least once per year. Only 38% (range: 24%–66%) of physicians test for NTM infection before initiating a macrolide monotherapy. Conclusions: Physicians need to be educated to screen patients with NCFB for NTM infection before initiating macrolide monotherapy. Recommendations for NTM-screening in these patients need to be validated, and further research on risk factors associated with NTM infection is warranted.